1995
DOI: 10.1063/1.469614
|View full text |Cite
|
Sign up to set email alerts
|

Direct femtosecond observation of the transient intermediate in the α-cleavage reaction of (CH3)2CO to 2CH3+CO: Resolving the issue of concertedness

Abstract: Articles you may be interested inObservation of charge-transfer excited states in the I−⋅CH3I, I−⋅CH3Br, and I−⋅CH2Br2SN2 reaction intermediates using photofragmentation and photoelectron spectroscopies J. Chem. Phys. 97, 5911 (1992); 10.1063/1.463752Reuse of AIP Publishing content is subject to the terms: https://publishing.aip.org/authors/rights-and-permissions. When a reaction involving two equivalent bonds has sufficient energy to break both of them, it can proceed by either a concerted or a stepwise mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 130 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Femtosecond studies of the lowest excited electronic state of acetone have shown the state to have a very short lifetime (<200 fs) leading to a high fragmentation yield [22,23].…”
Section: Photofragmentation Of Metal Cation/ketone Complexes At 266 Amentioning
confidence: 99%
“…Femtosecond studies of the lowest excited electronic state of acetone have shown the state to have a very short lifetime (<200 fs) leading to a high fragmentation yield [22,23].…”
Section: Photofragmentation Of Metal Cation/ketone Complexes At 266 Amentioning
confidence: 99%
“…The use of femtosecond transition state spectroscopy to detect the presence of reaction intermediates was introduced by Zewail and coworkers (84). Their time-resolved experiments on the α-cleavage reaction of acetone and on the decarbonylation of cyclopentanone have shown that both reactions proceed by a stepwise (nonconcerted) mechanism (85,86). In the condensed phase, the solvent provides a "cage" that keeps the reagents and products of a chemical reaction in close proximity, making it difficult to determine if a reaction proceeds by a concerted mechanism.…”
Section: Bound-free Transitions: Concerted-elimination Chemical Reactmentioning
confidence: 99%
“…The first ␣-cleavage occurs on a time scale (50 fs) shorter than a vibrational period, indicating * promotion is involved and IVR is circumvented. The second cleavage occurs on a longer timescale, suggesting that electronic to vibrational relaxation could take place before this cleavage [61]. Subsequent femtosecond experiments on a series of cyclic ketones have shown only a small dependence of Norrish Type I dissociation rates on ring size.…”
Section: Is the Initial Cleavage Nonergodic?mentioning
confidence: 99%